Biosystematic Studies on Amoebotaenia minuta sp. Nov. (Cestoda: Dilepididae) from Vanellus malbaricus - Bhure1, S.S. Nanware1*, R.M. Dhondge2; D.B. (Recent Research in Science and Technology, 2011)
The study focused on the observation of haematological parameters in Gallus gallus domesticus which is naturally infected with cestode parasites Cotugnia diagnopora. Out of 43 Gallus gallus domesticus, 28 are infected with cestode parasite. The significant increase in size of RBC and number of WBC; however reduction in the count of RBC, Hb, PCV, MCV in infected Gallus gallus domesticus as compaired with normal one. The haematological parameters of the infected bird Gallus gallus domesticus shows high infection cause macrocytic anaemia, lymphocytosis due to difficiency of related factors.